2010
DOI: 10.1016/j.regpep.2010.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Proghrelin peptides: Desacyl ghrelin is a powerful inhibitor of acylated ghrelin, likely to impair physiological effects of acyl ghrelin but not of obestatin

Abstract: Background. Proghrelin, produced by the ghrelin (A-like) cells of the gastric mucosa, gives rise to cleavage products, including desacyl ghrelin, acyl ghrelin and obestatin. The products are thought to be secreted concomitantly. In an earlier study we found acyl ghrelin and obestatin, but not desacyl ghrelin, to suppress the release of hormones from isolated islets of mouse and rat pancreas.Results. Using isolated mouse pancreatic islets to study the suppression of the spontaneous secretion of pancreatic polyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 62 publications
1
28
0
Order By: Relevance
“…These results suggest that DAG suppresses AG-induced food intake by preventing the increase in neuronal activity in the arcuate nucleus and recruiting nesfatin-1 immunopositive neurons (17). Kumar et al also reported the antagonistic properties of DAG on AG (19).…”
Section: The First Indicationsmentioning
confidence: 72%
See 2 more Smart Citations
“…These results suggest that DAG suppresses AG-induced food intake by preventing the increase in neuronal activity in the arcuate nucleus and recruiting nesfatin-1 immunopositive neurons (17). Kumar et al also reported the antagonistic properties of DAG on AG (19).…”
Section: The First Indicationsmentioning
confidence: 72%
“…Trophic and protective effects on β-cells in humans and rodents (16,21,55) Inhibition of ghrelin in humans and rodents (17,19) Restoration of EPC/CAC number and function in DM patients and rodents (40) Muscle regeneration in rodents (27,39) Des-acyl ghrelin (glucose) in humans and rodents (34,54) Figure 1 Overview of des-acyl ghrelin actions, along with some references for further reading.…”
Section: The First Indicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only acyl ghrelin binds to the growth hormone secretagogue receptor (GHS-R) 1a (7) [since then renamed ghrelin (GRLN) receptor (17)] to induce a GRLN receptor-dependent stimulation of gastric motility (21) and food intake (70) whereas desacyl ghrelin's actions are exerted independently of the GRLN receptor (60). Recent evidence indicates that coadministration of desacyl ghrelin counteracts the stimulatory effect of intrathecal injection of ghrelin on propulsive contraction of the rat colon (28), the orexigenic action of intraperitoneal injection of acyl ghrelin in rats (32), and the stimulation of pancreatic polypeptide (PP) secretion in isolated mouse islets (36) suggestive of a negative interaction between both peptides, although the physiological role of desacyl ghrelin is still to be established (33,60).…”
mentioning
confidence: 99%
“…An increasing number of studies suggest that desacyl ghrelin can act as a potent functional inhibitor of ghrelin [83]. It seems to antagonize ghrelin's effects on several functions including food intake [84,85]. Moreover, desacyl ghrelin can improve postprandial glycemia, especially in those subjects in whom preprandial acylated ghrelin levels are high.…”
Section: Other Stomach Hormonesmentioning
confidence: 99%